The Papuan Women's Participation Perspective in Political Leaders - Fitriani Fitriani; Rini Dewarusi Nebore; Poetri Enindah Suradinata (Musamus Journal of Public Administration, 2022)
This study observes that the participation of Papuan women in politics is very small to date, even after the government policy regarding women's representation of 30% and changes in cultural and customary perspectives in Papua towards the position of women still have not been able to increase the participation of Papuan women in the ranks of political leadership. , so that the purpose of this research is to describe how the perspective of Papuan women's participation in political leadership is. This study uses qualitative research methods by using literature/library studies that support the results of this study. The framework of this research uses the Longwe analysis approach (Sara Hlupekile Longwe) or commonly referred to as the Women's Empowerment Criteria or Women's Development Criteria, is an analytical approach developed as a method of empowering women with five analytical criteria. include: welfare, access, critical awareness, participation, and control. However, this research will focus on the cultural background and the dimensions of participation. The results of this study found that there was already participation of Papuan women in political leadership, but the number was still small due to external factors, especially the background in the form of an existing culture, and internally in terms of individual motivation who really needed a figure or role model.